Item Analysis Of Multiple-Choice Questions Of Pre-University Examination Conducted At Nobel Medical College - Joshi, B. R.; Rizal, S. (Devdaha Medical Journal, 2024)
Introduction: Multiple‐choice questions (MCQs) are useful in assessing student performance, covering a wide range of topics in an objective way. Its reliability and validity depend upon how well it is constructed. Item analysis evaluates the quality of test items using student responses to ensure they measure intended learning outcomes. The objective of the study was to assess the item and test quality of multiple-choice questions and to identify areas for improvement in test construction. Method: This is a cross-sectional observational study done to analyze 120 MCQs attempted by 100 MBBS students in their 2nd year pre-university exam (30 each from four papers). All the MCQs from 100 students were collected and evaluated using the correct keys. After the evaluation, the marks obtained by the students were entered in MS-excel and data analysis was done in SPSS. Each test paper was assessed for reliability, and individual items were evaluated using the difficulty index (DIF I) and discrimination index (DI). Results: The test papers demonstrated acceptable reliability, with KR-20 values ranging from 0.78 to 0.89. The mean difficulty index was 53.58 ± 17.84, with 65.84% of items falling within the acceptable range (DIF I 30–70). The mean discrimination index was 0.37 ± 0.18, with 46.66% of items showing excellent discrimination (DI > 0.4). Among the individual subjects, Biochemistry had the highest difficulty index (59.75 ± 21.27), while Physiology and Pathology had the highest discrimination indices (both 0.44). Only 5% of items were classified as defective. Conclusion: The analysis showed that most of the MCQs had acceptable difficulty and discrimination, indicating effective assessment of student performance. The study highlighted the need to review questions with low discrimination and extreme difficulty levels to improve overall assessment quality.